Vitamin D and Falls in Older African American Women: The PODA Randomized Clinical Trial. Issue 5 (30th January 2019) - Aloia, John F.; Rubinova, Rakhil; Fazzari, Melissa; Islam, Shahidul; Mikhail, Mageda; Ragolia, Louis
Abstract : Background: Limited information is available on the influence of vitamin D on falls in older high‐functioning black American women. Endocrine Society guidelines propose serum 25(OH)D levels over 30 ng/mL. Objective: To determine if maintenance of serum 25(OH)D above 30 ng/mL protects against falls. Design: The Physical Performance, Osteoporosis and Vitamin D in African American Women (PODA) trial had a prospective, randomized, placebo‐controlled, double‐dummy design with two arms: one with placebo and one with vitamin D3 adjusted to maintain serum 25(OH)D above 30 ng/mL. The primary outcomes were the prevention of bone loss and the decline in physical performance. Patients: The target population was healthy black women older than 60 years with serum 25(OH)D between 8 and 26 ng/mL. The trial was 3 years in duration with a falls questionnaire administered every 3 months. A total of 260 women entered the study, and 184 completed the 3 years. Mean age was 68.2 years. Setting: Research center in an academic health center. Main Outcomes Measure: Prevention of falls. Intervention: Participants were randomly assigned to placebo or active vitamin D. Vitamin D3 dose was adjusted to maintain serum 25(OH)D above 30 ng/mL in the active group using a double‐dummy design. Results: Baseline 25(OH)D was 22 ng/mL. Mean serum 25(OH)D reached 47 ng/mL in the active group compared with 21 ng/mL in the placebo group. There were 14.2% falls in the previous year recalled at baseline. During the study, 46% reported falling in the treatment group compared with 47% in the placebo group. There was no association of serum 25(OH)D or vitamin D dose with the risk of falling. Conclusions: There is no benefit of maintaining serum 25(OH)D above 30 ng/mL compared with the Institute of Medicine recommendation (20 ng/mL) in preventing falls in healthy older black American women. J Am Geriatr Soc 67:1043–1049, 2019.